1992
DOI: 10.1002/art.1780350607
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex genes and susceptibility to systemic lupus erythematosus in southern chinese

Abstract: Objective. To investigate the predisposing role of major histocompatibility complex (MHC) genes to systemic lupus erythematosus (SLE) in a Chinese population.Methods. Polymorphism in the HLA-DRB, DQB, complement component C4, and 21-hydroxylase genes was analyzed by restriction fragment length polymorphism analysis and oligonucleotide probing of in vitrwamplified DNA from 88 Chinese patients with SLE and 69 matched control subjects.Results. HLA-DRwlS and DQwl were significantly more frequent in patients (corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…[28][29][30][31][32][33][34] C4A*Q0 is also associated with SLE susceptibility in multiethnic Asian populations, including Japanese and Chinese. 35 This result has been replicated in Korean, 19 Japanese 36 and Chinese, 37 but also not in Chinese 16 and Malaysian. 38 However, C4A*Q0 is known to be in linkage disequilibrium with HLA-DR3.…”
Section: Resultsmentioning
confidence: 89%
“…[28][29][30][31][32][33][34] C4A*Q0 is also associated with SLE susceptibility in multiethnic Asian populations, including Japanese and Chinese. 35 This result has been replicated in Korean, 19 Japanese 36 and Chinese, 37 but also not in Chinese 16 and Malaysian. 38 However, C4A*Q0 is known to be in linkage disequilibrium with HLA-DR3.…”
Section: Resultsmentioning
confidence: 89%
“…In earlier days, the frequency of an 8.5 kb-HindIII band (corresponding to C4A gene deletion) was reported to be higher in SLE patients (20.5-24.5%) than in control individuals (7.9-12.9%) in the Caucasian population (Kemp et al 1987;Goldstein et al 1988;Reveille et al 1991;Hartung et al 1992), while in an AfroAmerican population, its frequencies were 14.5% in SLE patients and 3.7% in controls (Olsen et al 1989). On the other hand, this 8.5 kb-HindIII band itself was not observed in Japanese, Korean, or Chinese populations (Yamada et al 1990;Doherty et al 1992;Hong et al 1994), indicating that this particular allele was extremely rare or absent in Asian populations. Two basepair insertion mutations that would cause a premature stop codon in exon 30 of the C4A gene were reported in Caucasian SLE patients (Barba et al 1993;Lokki et al 1999), but we found such mutation in none of our SLE patients (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Fronek et al (7) and Doherty et al (6) described an association with HLA-DR2 and SLE nephritis in Americans. Lupus nephritis has also been associated with the HLA-DR3, HLA-DR15 and HLA-DR16 alleles in different ethnic groups (6,7,28). There is no description in the literature of an association between HLA alleles and SLE hematologic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have observed an association with HLA alleles and cutaneous or cardiac involvement (6). In addition, most studies showed an association between HLA-DRB1*02 and DRB1*15 and lupus nephritis, although HLA alleles have rarely been associated with SLE renal histologic class (3,4,6,7). The association with HLA and SLE in children appears to be similar to that observed in adults, but clinical involvement, autoantibodies and renal histologic class frequencies are quite different in these two groups (8).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation